APPLICATION OF PUBLIC MARKETING TOOLS IN THE FIGHT AGAINST ELECTRONIC CIGARETTE SMOKING AMONG TEENAGERS IN UKRAINE - BOCHKO, Olena (Herald of Khmelnytskyi National University. Economic sciences, 2022)
The increasing popularity of the use of electronic cigarettes and the possibility of reducing their consumption with the help of public marketing events make the writing of this scientific work relevant. Domestic scientists were mainly engaged in the study of the harmfulness of consumption and legal regulation of the circulation of electronic cigarettes, their excise taxation. However, these scientific works do not fully describe the comprehensive application of public marketing tools in the field of combating electronic cigarette smoking among teenagers. The scientific article describes the definition of the concept of demarketing, as one of the types of marketing in which public authorities can participate. The success of the implementation of two national information campaigns on the fight against tobacco smoking in Ukraine is analyzed. It was determined that it is most expedient to carry out such campaigns on the Internet, since teenagers actively use it. According to the author of the article, the success of the "There is no such thing as safe smoking" campaign could have been increased several times if targeted advertising was carried out in all popular social networks. Yes, videos were broadcast on YouTube, Facebook, but currently the youngest audience uses TikTok the most. Also, if the organizers of the information campaign had turned to popular video bloggers, and they, in turn, had briefly talked about the dangers of smoking electronic cigarettes in their videos, the success of the campaign would have been much higher. The article provides an example of how in Iceland, with the help of the implementation of the national plan "Youth in Iceland", the consumption of electronic cigarettes among teenagers was significantly reduced. And, Iceland became the European country with the lowest percentage of children and teenagers with bad habits. Based on this, possible ways to solve the problem in Ukraine using public marketing tools were proposed. The scientific article also provided recommendations for improving the use of public marketing actions in the field of combating e-cigarette smoking among teenagers in Ukraine.
Keywords: public marketing; public authority; demarketing; e-cigarettes; state